Strengthening Health Literacy to Prevent Risky Traditional Practices in Postpartum Care - Nurdiana Lante; Muh. Syafar; Syamsuar Manyullei; Yahya Thamrin; Shanty Rizkiyani; Andi Nilawati; Masni Mappajanci; Shrimarti R. Devy; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background : This study explores the tradition of postpartum care on Ternate Island to improve the behavior of preventing risky practices in postpartum mothers of the Ternate tribe through health literacy by implementing an integration model of traditional and modern practices through mentoring postpartum mothers and mama biang. This study aims to understand the level of knowledge of postpartum mothers and mama biang regarding the risks of dangerous traditional practices during the postpartum period and how health literacy can play a role in improving the behavior of preventing risky practices in postpartum care. Method: The method used in this study is the phenomenological method through focus group discussions (FGD) and in-depth interview techniques with 15 informants which aims to explore the informants' knowledge about the postpartum care tradition in the Ternate tribe. This study began in February-May 2024. Data collection used an unstructured interview questionnaire. The main theme was compiled to explore the knowledge of postpartum mothers and mama biang about the postpartum care tradition of the Ternate tribe. Results: The results of the study showed that the knowledge of postpartum mothers and mama biang related to the risks of traditional practices during the postpartum period is still very limited. The themes identified include knowledge, risks of unsafe care, perceived impacts, motivation, supporting factors for prevention efforts, maintaining cultural identity. In principle, they stated that every tradition carried out in postpartum care is considered good for recovery after giving birth , but sometimes ignores the threat of health risks so that the existence of mama biang in this concept must be empowered in aspects that do not conflict with medical. The findings have implications for the need for a cultural communication strategy to wisely shift traditional activities that have a negative impact on maternal health through local authorities. Conclusion: The conclusion of the results of this study is that it is necessary to improve health literacy among the people of Ternate Island, through the application of an integrated model of traditional and modern practices by providing training for assisting postpartum mothers and mama biang in order to improve behavior in preventing risky practices in postpartum care.